Pengaruh padat penebaran berbeda terhadap peningkatan produksi budidaya ikan lele (Clarias gariepinus) di kolam terpal - Indriani, Yeni; Saselah, Jetti Treslah (e-Journal BUDIDAYA PERAIRAN, 2025)
Cultivation of catfish (Clarias gariepinus) in tarpaulin ponds is a superior choice due to its flexibility and efficiency, but the optimal stocking density still requires further study. This study aimed to analyze the effect of different stocking densities on the production of catfish cultivated in tarpaulin ponds. The study was conducted using a completely randomized design (CRD) with three stocking density treatments: 50 fish/container (Treatment A), 100 fish/container (Treatment B), and 150 fish/container (Treatment C). Parameters measured included absolute length, absolute weight, and water quality. The results showed that stocking density significantly affected the absolute length and weight of fish. Treatment A produced the highest absolute length (16.92 cm) and weight (63.36 grams), followed by Treatment B (15.92 cm; 55.16 grams) and Treatment C (14.32 cm; 49.88 grams). Water quality parameters such as temperature, dissolved oxygen (DO), pH, nitrate, and ammonia generally remained within the safe range in all treatments, although quality decreased at higher stocking densities. This study shows that lower stocking densities provide more optimal production results in a tarpaulin pond system. Keywords: absolute weight, tarpaulin pond, water quality, absolute length